(untitled) (gjstudies, 2018)
This research introduces a novel, cross-disciplinary methodology for quantifyingand enhancing financial statement comparability across international jurisdictions,with the explicit aim of improving global investment decision-making. Moving beyond traditional accounting-based metrics, we propose a hybrid framework thatintegrates principles from computational linguistics, network theory, and machinelearning to construct a dynamic, multi-dimensional Comparability Index (CI). Thecore innovation lies in our treatment of financial statements not merely as numerical datasets but as complex semantic and relational documents. We employnatural language processing techniques to analyze the qualitative disclosures andmanagement discussion, network analysis to map the relational structure of accounting policy choices across firms and countries, and an ensemble of machinelearning models to predict the investment friction caused by comparability gaps.Our unique dataset comprises 5,000 firms from 40 countries over a ten-year period, enriched with geopolitical, regulatory, and cultural distance variables. Theresults demonstrate that our CI explains a significantly higher proportion of variance in cross-border investment flows, foreign institutional ownership, and mergerand acquisition premia than existing uni-dimensional measures. Furthermore, weidentify non-linear threshold effects and interaction effects with investor sophistication, revealing that the cost of low comparability is disproportionately borne by lesssophisticated investors. The findings challenge the prevailing assumption that harmonization of accounting standards (e.g., IFRS adoption) is the primary driver ofcomparability, instead highlighting the critical, and previously under-modeled, roleof enforcement regimes, disclosure culture, and the semantic coherence of financial narratives. This research contributes an original, computationally-groundedframework for a fundamental problem in international finance, offering actionableinsights for regulators aiming to reduce global market fragmentation and for investors navigating complex international information environments.